Effectiveness of Counseling in Increasing Mothers' Behavior (Knowledge and Attitudes) Regarding Post-Placental IUD Selection to Realize the SDG Goals of Good Health and Well-Being - Suharto, Agung; Nur Hanifah, Astin; Nurtatik (Universitas Airlangga, 2024)
Background: The low coverage of post-placenta IUDs is due to the non-optimal family planning counseling for third-trimester pregnant women. Aims: This study aims to analyze the effectiveness of ABPK and SKB counseling in increasing mothers' knowledge and attitudes about choosing a post-placenta IUD at Tawangrejo Health Center, Madiun City. Methods: This type of research is quasi quasi-experimental nonequivalent control group design. Data were analyzed using Marginal Homogeneity, Mann-Whitney, Mc Nemar, and Chi-Square. Results: The results showed that the Marginal Homogeneity test in the experimental group (SKB) obtained an increase in knowledge with a p-value of 0.000 (<0.05) and the control group (ABPK) obtained an increase in knowledge with a p-value of 0.000 (<0.05) so that it can be interpreted both effective in increasing the mother's knowledge about the selection of the Post Placenta IUD at the Tawangrejo Health Center. The result of the McNemar test on the attitude of the ABPK group was 0.227 (> 0.05) and the attitude of the SKB group was 0.146 (> 0.05) so it can be interpreted that both were not effective in increasing the attitude of mothers about the selection of the Post Placenta IUD at the Tawangrejo Health Center. The results of the Mann-Whitney test on knowledge after ABPK with knowledge after LCS show a p-value of 0.02 the mean rank at ABPK is 23 and the mean rank SKB is 28 meaning that there is a difference between ABPK counseling and SKB counseling in improving mothers' attitudes about choosing the Post Placenta IUD and counseling SKB is more effective. Conclusion: The conclusion of SKB counseling is more effective in increasing the mother's knowledge about the selection of the Post Placenta IUD at the Tawangrejo Health Center. Suggestions to further improve SKB counseling in Post Placenta IUD family planning services.